So-called Italianisms and their Etymological Status in Modern Standard Turkish Dictionaries - ALTUN, HİLAL OYTUN (Occhialì, 2021)
Italian-Turkish encounters date back to the 15th century and the first studies on language contacts between Italian and Turkish appeared in the 1890’s. With approximately 600 loanwords, Italian ranks fourth among donor languages for Turkish following Arabic, Persian and French. Italian is given as the source of 865 headwords in total in the dictionaries of modern standard Turkish that we have examined for this study, and 297 of their origin varies from one dictionary to another. The reason of this uncertainiy is that it is sometimes very difficult to distinguish the direct donor language from one that only acted as an intermediary. We offer examples for future lexicographic studies to demonstrate how structure of the lemma is used as an origin indicator leaning on the semantics